Synthesis of surfactant-coated cobalt ferrite nanoparticles for adsorptive removal of acid blue 45 dye - Mushtaq, Muhammad Waheed; Kanwal, Farah; Imran, Muhammad; Ameen, Naila; Batool, Madeeha; Batool, Aisha; Bashir, Shahid; Abbas, Syed Mustansar; ur Rehman, Ata; Riaz, Saira; Naseem, Shahzad; Ullah, Zaka (IOP Publishing, 2018)
Cobalt ferrite (CoFe 2 O 4 ) nanoparticles (NPs) are synthesized by wet chemical coprecipitation method using metal chlorides as precursors and potassium hydroxide (KOH) as a precipitant. The tergitol-1x (T-1x) and didecyldimethyl ammonium bromide (DDAB) are used as capping agents and their effect is investigated on particle size, size distribution and morphology of cobalt ferrite nanoparticles (CFNPs). The Fourier transform infrared spectroscopy confirms the synthesis of CFNPs and formation of metal-oxygen (M-O) bond. The spinel phase structure, morphology, polydispersity and magnetic properties of ferrite nanoparticles are investigated by x-ray diffraction, scanning electron microscopy, dynamic light scattering and vibrating sample magnetometry analyses, respectively. The addition of capping agents effects the secondary growth of CFNPs and reduces their particle size, as is investigated by dynamic light scattering and atomic force microscopy. The results evidence that the DDAB is more promising surfactant to control the particle size (∼13 nm), polydispersity and aggregation of CFNPs. The synthesized CFNPs, CFNPs/T-1x and CFNPs/DDAB are used to study their adsorption potential for removal of acid blue 45 dye, and a maximum adsorptive removal of 92.25% is recorded by 0.1 g of CFNPs/DDAB at pH 2.5 and temperature 20 ± 1 °C. The results show that the dye is physically adsorbed by magnetic NPs and follows the Langmuir isotherm model.